Association between polyunsaturated fatty acid intake and infertility among American women aged 20-44 years - Ruohan Wang; Ruohan Wang; Ying Feng; Jiahe Chen; Yingjiao Chen; Fang Ma; Fang Ma (Frontiers Media S.A., 2022)
BackgroundInfertility is a nationwide public health priority in the U.S. However, few studies have investigated the effects of dietary intake of polyunsaturated fatty acids (PUFAs) on female infertility. This study explored the association between PUFA intake and risk of infertility.MethodsA total of 1,785 women aged 20-44 years from three National Health and Nutrition Examination Survey cycles (2013-2018) were included in this cross-sectional study. The intake of PUFAs was obtained from a 24-h dietary interview on two separate days with a 3-10-day interval, and nutrient residue models were used. Fertility status was assessed by positive response to two relative questions via a questionnaire. Logistic regression models were used and some covariates were adjusted.ResultsAmong all the participants, 340 (19.05%) women suffered from infertility. The intake of docosahexaenoic acid (DHA) (OR = 0.998, 95% CI 0.998, 0.009) was slightly related to the risk of infertility. In contrast, women with higher α-linolenic acid (ALA) (OR = 1.416, 95% CI 1.138, 1.763) and linoleic acid (LA) intake (OR = 1.020, 95% CI 1.002, 1.038) presented with a relatively higher risk of primary infertility. Furthermore, in 20-34-year-old women, higher omega-6/omega-3 was significant associated with the risk of infertility (OR = 1.002, 95%CI 1.000, 1.005).ConclusionsOur results suggest that PUFA intake is only slightly associated with infertility. The higher the DHA intake, the lower the risk of infertility regardless of age. In women with primary infertility, ALA and LA has negative effect.